Phenology of Population of Immature Stages of Pear Psylla, Cαcopsyllα pyri, in the Region of Magnesia (Greece) - Stratopoulou, E. T.; Kapatos, E. T. (ENTOMOLOGIA HELLENICA, 1992)
The phenology of the population of immature stages of pear psylla, Cacopsylla pyri (L.), was studied in Greece (region of Magnesia), during the period 1988-1991 and it was found to follow a basic pattern. Pear psylla produces 5-6 gencrations per year. The first generation develops during the period February-middle April and it is quite discrets. Three overlapping generations are developed during the period front middle April until middle August but the amount of overlapping varies front year to year. Front middle August until the end of the season pear psylla produces 1-2 generations, i.e. only a part of the firth generation complotes the sixth one. Population density is generally low during the first generation but during May-June reaches verty high levels. During sommer, strong environmental pressure, supresses the population of pear psylla to low levels but it recovers again during September-October.